2017
DOI: 10.1097/01.aog.0000514110.66063.4a
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy as Gender-Affirmation Surgery in Female-to-Male Transgender Persons [37P]

Abstract: INTRODUCTION: Persons assigned female gender at birth may seek hysterectomy as part of their gender affirmation. Little is known about the characteristics and outcomes of this population. METHODS: Retrospective chart review of 15 trans men (female-to-male transgender persons), age 16-43, who underwent hysterectomy by a single surgeon at our academically-affiliated community hospital from 2012-2016. Three patients participated in a focus group aimed at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…It must be noted that this study was focused on the experiences of cis-gendered women. While the experiences of trans women undergoing hysterectomy as part gender affirming surgery are important and deserving of further scrutiny (Makhija & Mihalov, 2017), this is beyond the scope of this study.…”
Section: The Current Studymentioning
confidence: 99%
“…It must be noted that this study was focused on the experiences of cis-gendered women. While the experiences of trans women undergoing hysterectomy as part gender affirming surgery are important and deserving of further scrutiny (Makhija & Mihalov, 2017), this is beyond the scope of this study.…”
Section: The Current Studymentioning
confidence: 99%
“…With growing awareness at an individual and societal level, the medical fraternity is recognising gender diversity and their respective medical needs. 6 Understandably, changing medical vocabulary is a laborious process, but history has shown that changing terminology is possible. In 1961, the diagnostic term Trisomy 21, which some called 'Mongolism', had misleading connotations, and the World Health Organization dropped the word in 1965 after a request from the Mongolian People's Republic.…”
mentioning
confidence: 99%